NCMP-08. CLINICAL FEATURES OF CAR T-CELL THERAPY NEUROTOXICITY AS POTENTIAL SURROGATE MARKERS FOR PROGRESSION AND OUTCOME. (11th November 2019) - Yuen, Carlen; Artz, Andrew; Kelly, Thomas; Wu, Shasha; Reder, Anthony; Rezania, Kourosh; Soliven, Betty; Xie, Tao; Mastrianni, James; Park, Deric; Kosuri, Satyajit; Riedell, Peter; et al.
Abstract: : CAR T-cell therapy related neurotoxicity (NT) is common and can lead to fatalities. Early recognition may improve its management and treatment. METHODS: Twenty-six patients with relapsed/refractory diffuse large B cell lymphoma who received commercial CAR T-cell therapy (25 axicabtagene ciloleucel [Yescarta®], 1 tisagenlecleucel [Kymriah®]) between December 2017 and September 2018 were assessed for NT based on CARTOX-10 score and Common Terminology Criteria for Adverse Events (CTCAE) version 4. RESULTS: Twenty-three of 26 (88%) of patients developed NT, which was severe (Grade III-IV) in 8/26 (31%). Severe NT was associated with complete remission compared to progressive disease by both CTCAE (2.4 ±1.1 vs. 1.4 ± 1.3, p = 0.050) and CARTOX-10 score (8.3 ± 1.6 vs. 9.4 ± 1.5, p = 0.040). CARTOX-10 scores were lower for those transferred to the ICU compared to those transferred, respectively, on Days 8 (2.71 ± 4.78 vs. 9.28 ± 2.31, p = 0.010), 9 (2.71 ± 3.96 vs. 9.06 ± 2.50, p = 0.003) and 10 (2.86 ± 4.27 vs. 8.83 ± 3.37, p = 0.002). Depression was associated with poor overall survival (deceased 67% vs. alive 20%, p = 0.00004) and severe NT (severe NT 63% vs. non-severe NT 20%, p = 0.040). EEG findings of frontal intermittent rhythmic delta activity (FIRDA) in 22% (2/9) and triphasic waves in 33% (3/9) were exclusive found in severe NT. Tremulousness was present in 100% of severe NT compared to 67% of non-severe NT patients (p = 0.060). Delirium occurred in 2 patients, both of whom expired with severe NT. CONCLUSION: Depression, tremor, delirium, encephalopathy, and EEG features of FIRDA and triphasic waves may represent early clinical signs that predict the development of severe NT in off-protocol CAR T-cell therapy. Paradoxically, severe NT is positively correlated with progression free survival and may indicate effective therapeutic response.